ANALISIS MODEL DROPSHIPPING DALAM ETIKA BISNIS ISLAM - Yazida Salsabiila; Achmad Fajaruddin (Universitas Darussalam Gontor, 2020)
Dropshipping is one form of online business development that is now rife in demand by all business people throughout the world. This dropshipping model is not much different from online businesses in general, enough to capitalize on communication tools such as laptops or gadgets and the internet to access this business. The various facilities offered to the drop shipper are very interesting, some of them are like selling without capital, without stocking goods, and satisfying profits. The convenience offered by the dropshipping model is quite beneficial to the dropshipping offender. Whereas in Islam, humans are allowed to seek wealth by doing business. However, the search for this wealth in a way that is good and by the Shari'a, one of which reflects the axiom of Islamic business ethics in it. The purpose of this study is to analyze the activities and strategies of the dropshipping model and the application of the dropshipping perspective of Islamic business ethics. This research is qualitative research using the library method. The data taken for library research is taken from the exploration of library materials that are studied holistically. The results of this study indicate that the activities and strategies of this dropshipping model have fulfilled the axioms of Islamic business ethics. This is reflected in the model of cooperation between dropshipping actors, goods sold by the drop shipper, the suitability of selling prices, marketing of drop ship goods, and consumer transactions. But in reality, some drop-shippers don't do dropshipping properly. Resulting in various disputes between dropshipping actors and consumers. However, this research is far from perfect, hopefully, it can be perfected by further researchers.